Insulin resistance and lipid levels in the middle-aged offspring of parents with severe mental illness - Protsenko Maria; Kerkelä Martta; Miettunen Jouko; Auvinen Juha; Järvelin Marjo-Riitta; Jones Peter B; Gissler Mika; Veijola Juha (Elsevier, 2025)
Background
Type 2 diabetes and dyslipidemias co-occur frequently with severe mental illnesses (SMI). However, less is known about serum insulin and lipid levels and prevalence of Insulin Resistance (IR) in offspring with familial risk for SMI.
Method
The Northern Finland Birth Cohort 1966 consists of 12,068 mothers, 11,068 fathers, and 12,231 children from the two northernmost provinces in Finland. At age 46 they participated in clinical examination including measurements of glucose, lipids, and IR and answered a questionnaire including information about their nutrition and physical activity. The information on parental SMI was obtained from the Hospital Discharge Register. Parents with SMI were those who had been treated in hospital for any psychiatric disorder during 1969–1982 (ICD-8 codes 290–315). The final study group included 334 (7.3 %) offspring who had a parent with SMI and 4249 (92.7 %) offspring in the comparison group.
Results
We did not find increased risk for disturbances in lipid levels, insulin levels, or IR levels between the study group (offspring of either parent with SMI) compared with the comparison group. All offspring, especially female offspring of either parent with SMI, had an increased risk for higher glucose levels and waist circumference. The results remained the same after excluding offspring with SMI.
Conclusion
Our findings suggest that offspring of parents with SMI, especially female offspring, have partly increased risk for disturbances in cardiometabolic risk factors. Disturbances in glucose metabolism may have an effect via familial risk of severe mental illness.